KECERDASAN SPIRITUAL PROFETIK: MEMBANGUN KECERDASAN SPIRITUAL PROFETIKALA NABI MUHAMMAD - Ach. Maimun (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2022)
Artificial intelligence will replace a lot of human thinking tasks. However, the complexity of the humaninner aspect cannot be completely replaced by machines. Among those that cannot be replaced by machines is spiritual intelligence (SQ). This intelligence is considered to determine human happiness and success in living life. SQ introduced by Zohar and Marshall opened up space for the most important human potential. Islam presents a rich teaching about spirituality. This study focuses on the study of SQ Prophet Muhammad and how to build it. This is done on the teachings and history of life from the perspective of SQ theory. This study concludes that the spiritual intelligence of the Prophet Muhammad is a monotheistic religious spiritual intelligence that is based on the meaning of God's centrality in all existence. Humans are directed to interpret their lives as 'abid, khalifah, and 'amir by their roles as 'abd, khilafah, and' imarah. Developing spiritual intelligence is carried out by (1) studying Islamic teachings in-depth and broadly, (2) meditation on nature and God's majesty, limitations of self-quality, death, God's promises and threats to good and evil people, (3) istiqamah perform rituals such as prayer, dhikr, qiyam al-lail, fasting and controlling lust